Dasar-Dasar Fotografi Sebebagai Pembentuk Arsitektur Pada Perancangan Graha Fotografi - Rinjani, Frist Intan; Faisal, Gun; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Graha photography serves as a mediums to accommodate photography activities, but Pekanbaru City does not have a container that is devoted to that field, such as graha photography.Meanwhile, the development of photography is increasing from day to day, based on the fans and photography community. Some photography lovers learn about photography by self-taught, thus requiring individual containers to learn and develop. This is why we want to make graha photography in Pekanbaru City. Graha photography design is done by combining the definition of photography as a light of print and made the concept of design. Light print on the design of graha photography include the form of mass composition of the building as a transformation of the form that begins from the direction of light comes directed to the field of reflection to other fields until there are several times the reflection, such as the light of the digital single lens reflex camera. Meanwhile, the basic parts of photography composition, angle and moment apply to other building parts such as facades, landscaping and interior buildings.Keywords:, Light print, Photography, Reflection